MODEL OF SHARIA PRINCIPLES INTEGRATION IN THE APPLICATION OF CAPITAL MARKET LAW - Desy Nurkristia Tejawati; Fries Melia Salviana (Perspektif, 2017)
Indonesia is a country which most of the population is islamic, so of course in the life of the economy should be based on existing principles of sharia. At present, it must be admitted that the principles of sharia have grown in various fields of economy, including Banking, Insurance, and Capital Markets. However, in the Capital Market, although some of its instruments have been found in the Capital Market, the redulation is very minimal. This research is aimed at assisting Financial Services Authority in implementing Roadmap of Sharia Capital Market starting 2015 to 2019 to find a concept of Capital Market Law in accordance with Sharia Principles, so that Sharia Principles can be applied in isolation and different from Market Law regulation Conventional Capital that has been done. Research is a normative juridical research because it focuses on the rules of legislation using empirical data. The approach used is the approach of legislation and concept approach. Sharia Capital Market is a place for investors and emitents whose business field is not contrary to Sharia principles to conduct buying and selling activities in a way that uses the principles of sharia. The implementation of Sharia principles in Shariah Capital Market is in the business field of issuers, contracts used, and there are also arrangements related to Sharia Capital Market Experts.